Diagnostic Yield of Endoscopic Ultrasound-Guided Fine Needle Aspiration in Lung Lesions - Avinash Bhat Balekuduru; Yeluri Koushik; Kolangara Veetil Santhosh; Manoj Kumar Sahu (Journal of Digestive Endoscopy)
Background Tissue sampling from lung lesions is done by bronchoscopy, trans-thoracic needle aspiration lung biopsy, endoscopic ultrasound-guided fine needle aspiration (EUS-FNA), endobronchial ultrasound-guided FNA (EBUS-FNA), thoracenteses, or by surgery.